Self Efficacy dan Kecemasan Mengerjakan Skripsi pada Mahasiswa - Suyanti Suyanti; Albadri Albadri (PSYCOMEDIA : Jurnal Psikologi, 2021)
Thesis is a graduation requirement for students, of course it will cause some students to feel anxious at the moment working on. The anxiety could arise because of some things that are considered threatened. Besides anxiety can also arise due to low confidence in the ability of self or self-efficacy. This study was conducted to examine the correlation between self-efficacy with the anxiety of students who are working on the thesis. The scale used in this study is the scale of self-efficacy and anxiety scales. The subjects used in this research were 161 students from the Universitas Ibrahimy who was working on a thesis. The results showed a negative relationship between self-efficacy with anxiety in students who are working on the thesis with the calculated product moment correlation (r = -0.606, p = 0.000, p <0.01).